STUDY OF SHORT MACKEREL CATH, SEA SURFACE TEMPERATURE, AND CHLOROPHYLL -A IN THE MAKASSAR STRAIT - Bambang Semedi; Ratih Dewanti Dimyati (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2009)
The Makassar Strait is the major fishing ground for Short Mackerel (Rastrelliger spp) fisheries in South Sulawesi, Indonesia using both commercial fishing vessels and boats with traditional fishing gear. Though Short Mackerel is one of dominant commercial food fishes in South Sulawesi, the annual Cath per Unit Effort (CPUE) has been decreasing from year to year. In 2000, the total of annual CPUE was 22,117 tons and in 2007, it was 17,596 tons. The purpose of this research was to forecast the fishing ground of Short Mackerel employing Moderate Resolution Imaging Spectroradiometer (MODIS) satellite images in Makassar Strait territory with the study interest of 3 S and to 5 S and 118 E to 120 E. This research was conductade from September 15 to October 20, 2007. Fishing data were collected from the fishermen including fishing locations, catch, sea surface temperature, and chlorophyll concentrations. To determine the relationship between cacth and oceanographic parameters, linear regression was employed. We also examined sea surface temperature (SST) and Chlorophyll-a concentration field data vs. MODIS satellite data. The result showed that SST andChlorophyll distributions have close relationship with the distribution of fishing location of Short Mackerel. The fishing location tends to spread on the waters with the SST ranged from 26 degree of celcius to 29 degree of celcius and Chlorophyll concentration from 1.19 mg per m to 1.25 mg per m. Keywords: Chlorophyll-a, MODIS, Sea Surface Temperature.